Microstructure and properties of an as-deposited and heat treated martensitic stainless steel fabricated by direct laser deposition. (January 2017) - Fang, J.X.; Dong, S.Y.; Wang, Y.J.; Xu, B.S.; Zhang, Z.H.; Xia, D.; Ren, W.B.; He, P.
Abstract: A steel of 16 wt.% Cr-4.5 wt.% Ni-1.6 wt.% Mo-0.9 wt.% B-0.6 wt.% Mn-0.12 wt.% C was fabricated by direct laser deposition (DLD), and its microstructure and material performance were investigated using transmission electron microscope (TEM), scanning electron microscopy (SEM), electrochemical workstation, hardness and impact test machines. The results show that solidification process of the Fe-Cr-Ni-Mo-B steel did not follow the conventional phase diagram during DLD. The as-deposited microstructure consists of a martensite dendritic matrix and lots of lamellar eutectic phases. The lamellar eutectic phase is composed of carboboride and α phase. The carboborides were identified to be Cr-riched M23 (C, B)6 with face centered cubic (FCC) structure. Furthermore, the microstructure transition after heat treatment was also studied. After aging treatment, lots of nano-sized secondary carbides were dispersedly precipitated in the martensite matrix with a specific orientation relationship. The hardness is much higher than that of the as-deposited samples, but the toughness is decreased a lot. After destabilization treatment, the content of Cr in the interdendritic eutectic α phase increased and got close to that in the dendritic martensite. The interdendritic eutectic M23 (C, B)6 phase tended to be partially dissolved, spheroidized and finally transformed into elliptical-like particles with size of 100–500 nm. According to the high-resolution TEM results, the spheroidized carboboride was characterized with long period stacking (LPS) structure along 〈110〉 direction, which has not yet been found in the previous literature. In addition, the evolution of the chemical composition in various phases were also discussed. Due to the evolution of microstructure and chemical composition, both the corrosion resistance and impact toughness were improved significantly.